2012 International Conference on Biomedical Engineering and Biotechnology 2012
DOI: 10.1109/icbeb.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Removal of Copper, Zinc and Cadmium in Aqueous Solutions and Road Runoff by Carbonized Mulch: Heavy Metal Removal by Carbonized Mulch

Abstract: Carbonized mulch (CM) was used to remove copper (Cu), zinc (Zn) and cadmium (Cd) in solutions and urban road runoff in this study. Parameters investigated included pH, sorbent amount and reaction time. The removal of all three metals by CM was determined by pH and the peak at pH 5.5. The adsorption kinetics of all three metals by CM could meet the pseudo-first-order equation. The adsorption isotherms of all three metals by CM could be greatly described by Langmuir equation, as well as by Freundlich equation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Despite limitations of the pseudo first order model, this model has been successfully applied to describe the sorption kinetics of heavy metals on various biochar sorbents (Table 5). For instance, Zuo, et al (2012), reported that the pseudo-first order model closely reproduced data from the sorption of Cu, Cd, and Zn by carbonized mulch. Plotted kinetic curves for Cd, Zn, and Cu on the carbonized mulch, revealed a rapid sorption of these metals for the initial 30 min (typical for first order reactions).…”
Section: Pseudo -First Order Modelmentioning
confidence: 84%
“…Despite limitations of the pseudo first order model, this model has been successfully applied to describe the sorption kinetics of heavy metals on various biochar sorbents (Table 5). For instance, Zuo, et al (2012), reported that the pseudo-first order model closely reproduced data from the sorption of Cu, Cd, and Zn by carbonized mulch. Plotted kinetic curves for Cd, Zn, and Cu on the carbonized mulch, revealed a rapid sorption of these metals for the initial 30 min (typical for first order reactions).…”
Section: Pseudo -First Order Modelmentioning
confidence: 84%